Acronymizing eponyms: Where socio‑onomastic creativity outpacing morphological theory in naming male genitalia - Tur, Ajar Pradika Ananta (BAHASTRA, 2026)
This study investigates how Indonesian Instagram users craft male genitalia eponyms through acronymization, arguing that this practice is governed not by morphological rules but by socio-onomastic constraints. Analysis of 62 distinct names which were collected via phenomenological netnography and coded against Kridalaksana's sixteen acronym categories reveals that only four categories are attested, with 83.8% of items clustering in the "difficult to formulate" category. This concentration is not a classificatory residue but the central site of linguistic creativity, where users bypass structural regularity in favor of phonological naturalness and cultural salience. Rather than applying morphological rules to construct names, users select a culturally recognizable personal name as a target and retroactively manipulate source phrases to fit that onomastic template which is a process termed here as retrofitted eponymic acronymization. This bidirectional, name-driven process produces irregular acronyms that simultaneously function as taboo euphemisms, in-group solidarity markers, and performances of masculine identity in digital vernacular. These findings expose a fundamental inadequacy in Kridalaksana's framework, which presupposes linear rule-governed morphology and proves insufficient for digital taboo onomastics. The study calls for a hybrid typological model that integrates structural categories with a socio-onomastic creativity index accounting for taboo, identity, and digital context.